Densification Processes of Microalgae Bred for Biodiesel Production (Hungarian Journal of Industry and Chemistry, 2011)
An alga technology system has been developed, built and operated for the absorption of carbon dioxide and the production of biodiesel raw material. The main critical point in the technology is the separation of micro algae from the breeding medium (densification of the alga suspension). This is the most cost- and time-intensive part of the technology. The success of options in the literature, as well as further applicable phenomena and operations have also been studied. Along with flocculation, clarification and autoflocculation phenomena, special attention has been paid to membrane separation operations. Our aim is to devise a densification and separation process that has a low energy need and an advantageous operation time. The ultrafilter membrane splits the original mass flow (which consists of homogenized suspensions of different density) into two parts. One part passes the membrane, this is the permeate (deposited feed medium), the other is the concentrate, also called ‘retentate’ (in this case the concentrated alga suspension). This retentate can be easily and quickly cleaned of the accumulated metabolic products and remaining salt which can later cause a significant disturbance (at processing or in the following examinations). According to the assessment of the experimental results, the optimal solution seems to be membrane separation, on different grounds. It has a low energy need and an advantageous operation time and results in an appropriately clean suspension (i.e. void of metabolic products and salt). A PLC-controlled device equipped with a ZW-10 module was used for the densification experiments. The latter is the property of the Department of Chemical Engineering at the University of Pannonia.